The Influence of Educational Teacher- Learner Interaction on Adolescent Self-esteem - Meškauskienė, Asta (Pedagogika, 2017)
The teacher-learner interaction, which is of relevance to the contemporary learning paradigm, is grounded on goodwill, mutual respect as well as trust and enables a learner to become autonomous, proactive and responsible. The essence of the teacher’s activity can be determined in the following way: it is most important to focus on maturity of learners’ personality, development of their intellectual powers, their own active and conscious learning providing all the support necessary for learners to enable them to develop competences that are relevant in life. Next to such competences to be developed as learning to learn, communication and creativity, a particular role is played by personal competence, which targets at education and development of an individual, who is dignified, self-respected and able to adequately self-evaluate. There is a transition from the teacher’s role as the head of the process of education to those as a learning organiser, opportunity creator and advisor, when the development of learner’s autonomy, independence and responsibility become underlying values of education. Following educational researchers, there exists a close link between the learner’s self-esteem and autonomy and the freedom of choice provided by teachers. The teacher’s respect for learners, his/her attention, encouragement and positive expectations contribute to the strengthening of learner’s self-confidence and self-esteem.